Significance of 4D US parameters for the clinical treatment of female patients with stress urinary incontinence - Jiang, Changqin; Zhang, Song; Chen, Jing; Zhang, Yangyang; Cai, Keke; Chen, Wei; Wu, Yuanyuan; Liang, Chaozhao (Frontiers in Surgery, 2023)
Background Stress urinary incontinence (SUI) that has been associated with abnormal pelvic floor muscle function or morphology is a common condition. This research aimed to study the impact of the four-dimensional (4D) pelvic floor ultrasound on the treatment of female patients with clinical diagnosis of SUI and to evaluate its clinical significance on SUI. Methods We enrolled 51 women with SUI. Before transobturator suburethral tape procedures, the patients underwent 4D pelvic floor ultrasonography. The measurements include residual urine volume, bladder detrusor thickness in resting state, the vertical distance from the bladder neck to the posterior inferior edge of pubic symphysis at rest and Valsalva movement, posterior angle of bladder urethra, and urethral rotation angle. The degree of movement of the bladder neck (the difference between the vertical distance from the bladder neck to the posterior inferior edge of the pubic symphysis under the resting state and the maximum Valsalva movement) and the formation of a funnel at the internal orifice of the urethra were calculated. Results The mean bladder detrusor thickness was 2.6 ± 0.9 mm, the vertical distance from the bladder neck to the posterior inferior edge of pubic symphysis was 27.7 ± 4.5 mm, the posterior angle of the bladder was 122.7 ± 18.9°, the vertical distance from the rectal ampulla to the posterior inferior edge of pubic symphysis was 18.5 ± 4.6 mm, and the mean area of hiatus of the levator ani muscle was 22.1 ± 6.0 cm2. The mean posterior angle of the bladder on Valsalva was 159.3 ± 23.1°, and the mean urethral rotation angle was 67.2 ± 21.4°. Conclusions The 4D pelvic floor ultrasound is a reliable method in evaluating preoperational morphological characteristics of patients with SUI. With the help of the 4D pelvic floor ultrasound, the individualized treatment regimen can be developed and, more importantly, the inappropriate surgical decision can be avoided.